Quentin’s Personality Development in John Green’s Paper Towns - Ila Nuriya Habibah; Muhammad Thoriqussuud; Abdur Rohman; Fathur Rohim; Abu Fanani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The purpose of the study is to explain Quentin’s personality before meeting Margo and how it is after meeting Margo in John Green’s Paper Towns. The main character, Quentin, changes from being static person in life such as having no ambitions, being a coward person, and disciplined one before meeting Margo to being a dynamic person such being an ambitious person, being a brave person, and being an insubordinate one after meeting Margo. The kind of change in life draws the researcher’s interest to conduct the analysis in this article since human’s thought develops from time to time whose developments could do the person either harm or good. However, this personality change does the main character good. Using emotional and social determinants and close reading method, the researcher conducts a deep observation about the main character’s personality and finds its change from unambitious, coward, and discipline before meeting Margo to ambitious, intrepid and insubordinate after meeting Margo. Thus, two of the eights determinant give a significant change of life of the main character, therefore, such determinants are worth studying very deeply as such knowledge is very necessary to make people able to manage available determinants they encounter in their daily life. Finally, the finding is to develop the theory of literature in application, namely, the personality development by Hurlock.